Bifurcation of cycles of parabolic systems with retarded argument and small diffusion - Klevchuk, I.I. (Yuriy Fedkovych Chernivtsi National University, 2015)
We prove the existence of periodic solutions in autonomous parabolic system of differential equations with retarded argument and small diffusion on the circle. We consider the problem of existence and stability of traveling waves. We obtain the bifurcation equations.
Біфуркація циклів параболічних систем із запізненням та малою дифузією
Клевчук, І. (1). Біфуркація циклів параболічних систем із запізненням та малою дифузією. Bukovinian Mathematical Journal, 3(2). Retrieved from https://bmj.fmi.org.ua/index.php/adm/article/view/142
Keywords: parabolic system of differential equations; stability; traveling waves; bifurcation equations